Compression behavior of a novel sandwich structure with bi-directional corrugated core. (April 2021) - Ge, Lei; Zheng, Huayong; Li, Huimin; Liu, Baosheng; Su, Haoran; Fang, Daining
Abstract: A novel sandwich structure with bi-directional corrugated core is designed and manufactured by 3D-printing. Initial attention focuses on the compression response and failure modes of this new structure. An analytical model is developed and verified by experimental and finite element methods (FEM). As a comparison, compression properties of the conventional sandwich structure are also tested under compression loading. Results show that the corrugation bucking and fracture are the main failure modes in the flatwise compression. However, the loading in edgewise direction is mostly supported by face panels, and obvious deformation is not observed. There is no debonding between the face panels and corrugated core under the continue loading, which means a well-bonding quality is achieved. The predicted results by analytical model show good agreements with those by FEM and experimental method. It has been proved that the stretching deformation is dominating in the deformation mechanism of flatwise compression. As for the edgewise compression, it finds that the corrugations paralleled to the loading direction are the main load-bearing structure. This novel sandwich material with bi-corrugated core owns better compression properties than the conventional one with single-corrugated core. Graphical abstract: Image 1 Highlights: A novel sandwich structure with bi-directional corrugated core is proposed. The novel sandwich structure is manufactured by 3D-printing. Analytical model of the compression elastic modulus is derived and verified. The deformation process and failure modes are fully investigated. New sandwich structure owns better compression property than conventional one.